Clinical characteristics and management of immune checkpoint inhibitor‐related pneumonitis: A single‐institution retrospective study. (19th November 2020) - Wang, Hanping; Zhao, Yanwei; Zhang, Xiaotong; Si, Xiaoyan; Song, Peng; Xiao, Yi; Yang, Xu; Song, Lan; Shi, Juhong; Zhao, Haitao; Zhang, Li
Abstract: Introduction: The increasing application of immune checkpoint inhibitors (ICIs) will cause more checkpoint inhibitor‐related pneumonitis (CIP), which is a common cause of ICI‐related death. The clinical management of CIP needs further optimization. Methods: Patients who were managed at Peking Union Medical College Hospital (PUMCH) between February 2017 and December 2019 with a diagnosis of CIP were retrospectively analyzed. Clinical data including clinical manifestations, radiologic data, laboratory and bronchoscopy results, treatments, and outcomes were collected and analyzed. The Mann–Whitney test was used to compare patients with and without co‐infections. Results: In total, 48 CIP cases in 42 patients were analyzed. The median time from the first dose of ICI to the onset of CIP was 1.9 months (range: 0.1–13.7). Grade 3–4 (G3–4) accounted for 30 cases (71.4%). The most common symptoms were cough (88.1%) and dyspnea (78.6%). The median starting dose of equivalent prednisone (EP) was 55 mg (range: 30–200) for all patients. The median total duration of glucocorticosteroids (GCS) treatment was 42.5 days (range: 15−89). Three patients (7.14%) died because of infection. A higher starting dose and longer duration of GCS (≥30 mg/day; p  = 0.001) were associated with opportunistic infection. Chest computed tomography (CT) showed diverse and asymmetrical lesions. Twelve patients were re‐challenged, and six patients developed recurrent CIP. Conclusions: The clinical and imaging manifestations of CIP are various, and differential diagnosis of exclusion is essential. GCS at 1–2 mg/kg is feasible to treat CIP, but the duration of GCS ≥30 mg/day should be used with caution, given the high risk of acquired infections. Re‐challenges of ICI are feasible, but the recurrence of CIP needs to be closely monitored. Abstract : This study revealed for the first time the clinical characteristics, diagnosis, and treatment of CIPs in Chinese cancer patients. The recommended starting dose of 1–2 mg/kg GCS is feasible, but the duration of GCS ≥30 mg/day should be controlled, as acquired infections during the GCS treatment rather than refractory CIP could be the main cause of CIP‐related deaths.